A field application of physically-based erosion and sediment transport model for hillslope response - Yoon, Jaeyoung; Aksoy, Hafzullah; Kavvas, Levent; Arguelles, Anya Catherine C.; Mallari, Kristine Joy B. (Informa UK Limited, 2014)
A physically based erosion and sediment transport component is developed for hillslope-scale hydrologic model. In so doing, this study aims to apply the modeling approach that takes the rill and interrill connection into account to reflect more realistic hillslope configuration. Erosion and sediment transport modeling at such a fine resolution is rare and seldom verified especially at field scale. For interrill areas, it uses the kinematic wave equation for flow. For sediment, the one-dimensional width-averaged sediment mass conservation equation is used, which was derived from its two-dimensional form by performing local-scale averaging. Rills are conceptualized as micro channels with rectangular cross sections. Flow in rill is accordingly modeled by cross-sectionally averaged kinematic wave equation. Sediment transport formulation within a rill uses the continuity equation in one-dimensional form. By considering the connection between the rills and interrill areas, the model was calibrated and validated using field data set collected from a hillslope section in Northern California. The calibration produced r2 and NSE values of 0.92 and 0.89, respectively; while validation results produced 0.82 for the r2 and 0.66 for the NSE. It is found from the simulations that the model performed well both in calibration and validation and promises to be a useful erosion and sediment transport model for hillslope response.